PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN KAFE DINGIN PULUNG DI KECAMATAN PULUNG KABUPATEN PONOROGO - Sanjaya, Aurelia; Gunadi, Belinda; Sutanto, J.E. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The culinary business in Ponorogo is growing rapidly, including the Dingin Pulung Cafe which is experiencing sales fluctuations due to customer dissatisfaction with product quality, price, and service quality. The main objective of this study is to establish the level of impact of product quality, price, and service quality have on the level of customer satisfaction at Dingin Pulung Cafe. This research uses a quantitative approach, collecting responses via surveys from 180 purposively sampled respondents who meet certain criteria. The sample criteria in this study were customers who had purchased products at Dingin Pulung Cafe 1 to 2 times in the last month. Data analysis was conducted using SPSS 26 to ensure accurate results. In this study, the data collection technique involves using Google Form with a Likert scale, which allows to measure respondents' perceptions of products, prices, and services provided. Multiple linear regression serves as the analysis method, which makes it possible to examine the impact of these variables simultaneously. The findings from the regression analysis indicate that product quality, price, and service quality significantly affect customer satisfaction. In addition, the three factors together also make a significant contribution to customer satisfaction, with a coefficient of determination of 70.8%.